MARINE TURTLE CONSERVATION PROGRAM AT PUERTO PRINCESA SUBTERRANEAN RIVER NATIONAL PARK: CHALLENGES AND OPPORTUNITIES DURING COVID-19 PANDEMIC - Liwayway Acero (BIOTROPIA, 2023)
The Puerto Princesa Subterranean River National Park (PPSRNP)-Marine Turtle Conservation Program (MTCP) can be found in West Coast of Palawan Philippines. Geographical location is located in the global center of marine biodiversity, the Coral Triangle. This study described the profile of PPSNRP-MTCP in terms of location, species of marine turtles, number of hatchlings released per year, management organizational structure, conservation activities and, determined the perceived management challenges and opportunities encountered by employees during COVID 19 pandemic. Documentary analysis, net-notgraphy and focal group virtual discussion and structured questionnaires were used in data gathering. There are 3 species that were recorded in the conservation site; Chelonia mydas, Eretmochelys imbricata and Lepidochelys olivacea. Hatchling success from 2015 to 2021 is at an average of 82%, and the mean hatchlings per year is 1659.4 (+/- sd.699.31). Lowest was 697 in 2014-2015, highest in 2019-2020 with 2,476 hatchlings. MTCP is under the supervision of Protected Area Superintendent (PASu). The management activities are; regular monitoring of egg nesting and hatching of the eggs, implementation of easement zone, community coastal clean-up, releasing of hatchlings and conservation awareness campaign. Debris left by typhoon Odette is the perceived very high challenge while the absence of noise during nesting season is perceived at a very high opportunity.